Regional Security in Africa The Dynamic and Challenges - Zakiyah Zakiyah (Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : This article examines the idea of how the African Union (AU) and its aspects of security agency in Africa including APSA in dealing with the issue of security. As it is the fact that many countries in this region have experienced conflicts either within state or intra states. The data says that about 64 percent of the nations in this continent had engaged in conflicts or wars in the last fifty years. Therefore, there is a notion mentioning that Africa should solve their problems through its regional security. On the other hand, there is an opposite argument saying that the AU should not be left alone because they have no sufficient resources, fund and peacekeepers to conduct their missions. Thus, this paper argues that partnership between the regional security in Africa and the international agency like the United Nation (UN), the European Union (EU) will be one of alternative solutions for African problems. This partnership can be seen from some missions such as the deployment of troops in Burundi in which it was funded by the UN, while the AU provided troops coming from South Africa, Ethiopia and Mozambique. Another partnership between the AU and an international agency can be looked at the mission in Darfur Sudan which was funded by the EU.Keywords: African Union, regional security, peacekeeping, conflicts